"Games with learning": adpositions and the lusory attitude. Issue 3 (8th August 2016) - Duncan, Sean C.
Abstract : Purpose: Games and learning research has diverged into "games for learning" and "games as learning" research. This paper aims to provide a third framing, "games with learning", that can help address the lived experiences learners have with these media outside of formal, instructional contexts. Design/methodology/approach: This paper is a critical analysis of the current games and learning field, considering what has been missed by recent research in the field and how we might benefit from further consideration of what Bernard Suits calls the "lusory attitude" or voluntary choice to accept inefficiencies in achieving goals. The paper analyzes dominant rhetoric of educational game research, with the intent of revealing the implicit assumptions about play and choice that much recent "games for learning" and "games as learning" work may have ignored. Findings: The paper reveals that the further consideration of learning through extant play with games (characterized here as "games with learning") can be a means of shifting the direction of educational games research toward investigations of how games are played "in the wilds" of out-of-school contexts. The paper advocates for a shifting of focus from compulsory contexts to the study of voluntary game play. Social implications: The paper argues for the complex value of games and gameplay in non-institutional settings, and advocates for further research to understand games in non-institutional spaces. Originality/value: The key argument is that games and learning to date has focused inordinately on how games can further educational design, rather than how the use of games can reveal important new contexts for learning.